Anthropogenic modification of the natural fire landscape and its consequences for vegetation patterns on the Cape Peninsula - Rogers, Annabelle J (Department of Biological Sciences, 2017)
Understanding the spatial probability of fire and how urban development may alter natural patterns is particularly important in areas where alternate ecosystem states occur at fine spatial scales. The Cape Peninsula, South Africa, is a one such region where fire-sensitive forest patches occur interspersed in a sea of fire-dependent fynbos. Fire is believed to be an important determinate of forest distribution, with absence or occurrence of fires potentially allowing patch contraction and expansion. In this thesis I use a series of computer models to determine the extent to which anthropogenic development and land transformation have altered the spatial variation in fire likelihood, or the 'burn probability', and its consequence for the distribution of forest on the Cape Peninsula. The two multi-model, fire behaviour simulation systems I use are FlamMap and FARSITE. FARSITE is a deterministic simulation package used globally for discrete event simulation. In an effort to assess the viability of using the FARSITE model for fire prediction in fynbos and the determinants of model accuracy, I predicted fire area for a historical fire on the Cape Peninsula using a variety of fuel models and wind conditions. Following this validation, FlamMap was used to simulate the burn probability of the Cape Peninsula under natural conditions – no urban development present – and transformed conditions – where urban areas mapped as non-burnable fuel models. I then determined changes in forest distribution documented over the last 50 years relative to changes in burn probability as a result of urbanisation. My results show that an increase in urbanisation on the Cape Flats has produced a significant urban shadow effect due to the interruption of natural fire catchments. This urban shadow effect has resulted in an overall increase in area of fire refuges on the Peninsula and expansion of forest, particularly on the more mesic eastern slopes at Kirstenbosch and Newlands. The results strongly support that urban-mediated changes to fire patterns are drivers of forest expansion in this region, and adds further evidence to support the significance of fire in determining biome boundaries in the fynbos.